а)
8x^2-4x-x^2+9
7x^2-4x+9
b)(р+3)(р-11)+(р+6)²
p^2 -8p-33+ p^2+12p+36 = 2p^2+4p+3
в)7(а+b)²-14 ab
7a^2+14ab+7b^2-14ab=7a^2+7b^2
2. Разложите на множители:
а) γ³-49γ ; б) -3а²-6ab-3b²
a)y(y^2-49)=y(y-7)(y+7)
б) -3а²-6ab-3b² =-(3a^2+6ab +3b^2)=-3(a+b)^2
3. Упростите выражение:
(а-1)²(а+1)+(а+1)(а-1) и найдите его значение при а= -3
16*-2+8=-32+8 =-24
а) (γ-6)²-(3γ)² = (y-6-3y)(y-6+3y)
б) с²-d²-c-d =(c-d)(c+d) - (c+d)=(c+d)(c-d-1)
(х-γ)² + (х+γ)²=2(х²+γ²)
x^2-2xy+y^2+x^2+2xy+y^2=2(x^2+y^ 2)
2x^2+2y^2=2 (x^2+y^2)
Объяснение:
1)
5x³ + 20x² - 25x = 5x · (x² + 4x - 5) = x · (x² + 4x + 4 - 9) = x · ((x + 2)² - 3²) = x · (x + 2 - 3) · (x + 2 + 3) = x(x - 1)(x + 5)
2)
3a³b³ - a⁴b⁴ + 2a³b⁸ = a³b³ · (3 - ab + 2b⁵)
3)
5m + 5n + mn + n² = 5·(m + n) + n·(m + n) = (m + n)(n + 5)